Tanjungpinang Creative Hub Dengan Pendekatan Arsitektur Ekspresionis - Syilvia Ovtariyani Putri; Pedia Aldy; Mira Dharma Susilawaty (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Tanjungpinang Creative Hub is a central that can accommodate creative activities in the development of network, organization and business of creative industries. Tanjungpinang as the capital of Riau Islands Province is potentially to the development of creative economy due to the technological advancement in creative industry growth and tourism, both in the field of art products, culture and local wisdom. So many creative actors and micro enterprises emerge active in the creative industry sectors. Creative hub planning becomes the solution of the problem that serves as an educational, commercial and recreational facilities and there are supporting facilities for user activities. Tanjungpinang Creative Hub facilitates the development of seven creative industry subsectors namely performing arts, fashion, culinary, crafts, photography, animation and graphic design. This method uses expressionist architectural approaches to provide an expressive and imaginative image of the building when anyone sees it as well as being able to present building functions as a place of shaping creativity and enriching self-expression. Implementation of expressionist architecture by applying the characteristics and values to the design of the building through three elements namely façade, interior, floor plan and building mass. The concept used is Unity in Creativity that expresses the meaning of a universal form of creative into a harmonious unity, based on the dimension of creativity that can be manifested through the character, emotion and innovation into architectural form. keywords : Tanjungpinang, Creative Hub, Expressionist Architecture, Unity in Creativity